DAMPAK KELANGKAAN BAHAN BAKAR MINYAK TERHADAP STABILITAS EKONOMI DAN MOBILITAS MASYARAKAT DI INDONESIA: KAJIAN PUSTAKA KEBIJAKAN ENERGI NASIONAL - Loso Judijanto; Abdul Jalil Hutagalung; Era Purike (CV. Lafadz Jaya, 2026)
The fuel shortage in Indonesia has far-reaching implications for economic stability and public mobility, whilst also highlighting the limitations of national energy policy in addressing excessive reliance on fossil fuels. This literature review examines how supply pressures, price rises and fuel subsidies trigger inflation, place a strain on the state budget, disrupt the real sector and undermine the investment climate, thereby reducing macroeconomic resilience. On the other hand, fuel shortages also hinder public mobility, particularly in terms of access to education, healthcare, employment and social activities, whilst widening socio-economic disparities. This article concludes that the sustainability of economic stability and social mobility requires the strengthening of national energy policies that are more oriented towards energy diversification, efficiency and the enhancement of more energy-efficient public transport modes.